(3EYQGH CeKdI GdJMaI GdSfjI dbQGA GdCLQhejIs - (3jMji Hf eMeO GdeSGdMis; (3GHf GLQhe , CHh YHO Gddg eMeO Hf eMeO Hf OGhO GdUfgGLj,J (B723 (3g` s ((3eUWai Hf GdSjO TQja GdeQGOjfi s)
(3ChdgG (B:s
(3GdcdeI NeSI CbSGe (B: (3GSe haYd eGVi , haYd eVGQY , haYd CeQ , hMQa , hdcd hGMOI efGdNeSI YdGeGJ JejRgG Yf CNhGJgG s
(3BNQgG (B:s
(3hZdG ajchf (B" (3JcQe (B" (3HOd ZTJeGd , hHGbi GdEYQGH Ydi MGdg , hGdgd CYde HGdUhGH hZdjg edQLY hGdeBH Je HMeO Gddg hYhfg hMSf Jhajbg s
(3HgG fXGe GdJYbjHIs
(3cJH HYV cdeGJgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B33 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B215s
Keywords: (3GdfMhs